Dampak Kegagalan Layanan Terhadap Minat Beli Ulang dan Kepuasan Pelanggan Shopee Xpress Bandung Raya - Saprudin, Azbi Ziesha; Rahman, Aulia Zikri; Komaro, Mumu (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effects of service failure and service recovery on customer satisfaction and repurchase intention among Shopee Xpress users in the Greater Bandung area. Using a quantitative approach with PLS-SEM via SmartPLS, data were collected from 150 active users. Results show that both service failure and service recovery significantly affect customer satisfaction but do not directly influence repurchase intention. Customer satisfaction has a strong and significant effect on repurchase intention and mediates the relationship between service failure and recovery toward repurchase behavior. These findings highlight the importance of service quality improvement and responsive recovery strategies to build customer loyalty in Indonesia’s competitive e-commerce logistics sector.